Polarization of Σ+ hyperons produced by 800 GeV/c protons on Cu and Be - Pogodin, P.; Alkhazov, G.; Atamantchouk, A. G.; Balatz, M. Y.; Bondar, N. F.; Cooper, P. S.; Dauwe, L. J.; Davidenko, G. V.; Dersch, U.; Dolgolenko, A. G.; Dzyubenko, G. B.; Edelstein, R.; et al. (American Physical Society (APS), 2004)
We show that Σ+ hyperons produced by 800 GeV/c protons on targets of Be and Cu have significant polarizations (15-20%). These polarizations persist at values of pt = 2 GeV/c and a wide range of xF. The polarizations from the Cu target are consistently less than from Be. The average ratio of the Σ+ polarization from Cu to that from Be is 0.68 ± 0.08.
Keywords: beryllium; copper; dipole; magnet; magnetic field; neutron; polarization; proton radiation